ON THE RELATIONSHIP BETWEEN GLOBALIZATION AND THE LITERARY PROCESS - Sabirova, Zebo (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2023)
The article analyzes the emergence of the "globalization" phenomenon and the historical, socio-political, cultural, and literary processes that paved the way for its formation. As the development of computer technologies covers the daily life of the world community, it affects the material and spiritual needs of a human being, which is the main character of the artistic work. The study discusses the present and future of national literature, which express the behavior and actions of modern people. The purpose of the research is the main characteristics of Uzbek poetry in the era of globalization and the relationship between the literary process, the main characteristics and principles of the poetry of the period, internet literature and poetry, creative attitude to tradition and innovation, the style and individuality of the creator, observed in form and content.
Keywords: globalization process; national literature; fiction; psychological analysis; literary process; thinking and imagination; globalization of literature; fate of national literature